Discriminant Function Techniques to Study the Fertility Differences in Flood Sediments and the Original Soil in Jaipur Region - Kolarkar, A S; Sharma, B K; Gupta, B S; Taimni, Vishnu (Annals of Arid Zone, 2016)
July 1981 flood in Jaipur region deposited massive sediments on the productive lands; burying the fertile soils below. An attempt has been made to examine statistically how far these two soil types namely-soils of flood sediments and the soils buried below, differ from each other. Samples from 53 sites for both the soil types were analysed for various soil fertility characteristics. Fisher’s linear discriminant function as well as Mahalanobis D2-techniques were applied to study the relative contribution of these characteristics in discriminating the two soil types. Fisher’s discriminant function came out to be significant at 1 per cent probability level. The relative weights of organic carbon, copper, and manganese help in differentiating the two soil types. Mahalanobis D2-the distance between two’ soil types, worked out at 1357.452 was found to be significant. Manganese, organic carbon and iron accounted for 44.32, 37.04, 32.67 and 10.51 per cent, respectively of the total distance between flood sediments and the original soil.